Computed tomography-guided cryoablation for functional adrenal aldosteronoma. Issue 3 (1st June 2021) - Fu, Yu-Fei; Cao, Chi; Shi, Yi-Bing; Zhang, Wei; Huang, Ya-Yong
Abstract: Purpose: To assess the safety and clinical effectiveness of computed tomography (CT)-guided cryoablation for functional adrenal aldosteronoma. Material and methods: From June 2012 to December 2018, 11 patients with functional adrenal aldosteronoma underwent CT-guided cryoablation in our center. Data comprising complete ablation rate, clinical success rate, procedure-related complications and long-term outcome were collected and analyzed. Results: A total of 11 aldosteronoma in 11 patients were treated. Complete ablation was achieved in all patients after a single ablation session. No procedure-related complications occurred. Clinical success rate was 100%. Mean aldosterone levels, and systolic and diastolic pressure decreased from 858.6 ± 93.2 pmol/L, 156.4 ± 7.8 mmHg and 90.0 ± 10.5 mmHg prior to treatment, respectively, to 321.8 ± 41.2 pmol/L ( p < .001), 129.1 ± 9.4 mmHg ( p < .001) and 76.4 ± 5.5 mmHg ( p = .005) after treatment, respectively. Mean renin and potassium improved from 0.2 ± 0.1 μg/L/h and 2.9 ± 0.2 mmol/L before treatment, respectively to 4.6 ± 0.4 μg/L/h ( p < .001) and 4.2 ± 0.2 mmol/L ( p < .001) following treatment, respectively. No tumor or clinical symptom recurrence occurred during the follow-up. Conclusions: CT-guided cryoablation is a safe and effective method for the treatment of functional adrenal aldosteronoma.